Compreensão de conjunções por alunos do 8º ano do Ensino Fundamental a partir da aplicação do teste cloze - Silva, Rosemeire Pedro da (2020)
The theme of this study is the understanding of conjunctions by students in the 8th year of elementary school based on the application of the cloze technique. For this study, two groups of participants were selected: the experimental group (EG) and the control group (CG). So, the present study is interested in analyzing whether the understanding of conjunctions, by eighth grade students, will help them during the process of reading comprehension of a text, and this will be accomplished through the application of two activities called Pre-test and Post-test. The research presented here uses the action research methodology, which represents a logical and systematic sequence of intended steps, according to Tripp (2005). In this way, we were inspired by this methodological model, and we structured our work, from the division of the development process, in three distinct stages, which were called diagnostic, interventional and evaluative. The planning was structured in eight meetings of two hours / class each, making a total of sixteen hours / class in eight weeks. Meetings 1 and 8 refer to the pre-test and the post-test, respectively, in which the two groups participated, GE and CG. And meetings 2 to 7 refer to the intervention phase, only with the GE. The research was applied at a primary school in the city of Fortaleza-CE. The theoretical framework of this work was formed from studies on reading as a process of construction of meanings (Barbosa, 1994; Smith, 2003); reading comprehension (Koch & Elias, 2006; Kleiman, 2002), textual cohesion (Koch, 2002; Halliday & Hasan, 1976; Koch, 2005), the cloze technique (Santos, Primi, Fee & Vendramini, 2002; Oliveira; Boruchovitch & Santos, 2009B) and the use of conjunctions (Cunha and Cintra, 2001; Bechara, 2009; Azeredo, 2001) we still present the guidelines on conjunctions provided by the official documents that regulate education in Brazil, we have focused on the approaches of the National Pact for Literacy at the Right Age – PNAIC, the Common Base National Curriculum - BNCC and the Ceará Reference Document - DCRC. It should be noted that there are still no studies on the understanding of conjunctions by students. After analyzing the results, we could see that the interventional activities had a positive influence on the students' learning, about reading comprehension, as well as the use of conjunctions.